Noah in the Animal Apocalypse (1 En. 89:1-9) - Drawnel, Henryk (The Biblical Annals, 2024)
The Aramaic description of the flood in 1 En. 89:1–9 has survived in two fragments from Qumran (4Q206 frg. 8 I and frg. 9), which contain a shorter text than the Ethiopic translation. This article is an analysis of the presentation of the figure of Noah in the longer version of the Ethiopic Animal Apocalypse in the context of the Ethiopic Book of Enoch and in relation to Mesopotamian traditions associated with the flood. After being told the secret about the flood by a “man” (an angel), Noah, the white bull, works as a carpenter and builds a huge boat. After the flood, transformed into a “man” (a supernatural figure in the symbolism of the Animal Apocalypse), he leaves his three sons. This description of Noah brings him closer to the main characters of the flood in Mesopotamian sources.